A Cadaveric Study Evaluating the Feasibility of an Ultrasound-Guided Diagnostic Block and Radiofrequency Ablation Technique for Sacroiliac Joint Pain. Issue 1 (1st January 2017) - Roberts, Shannon L.; Burnham, Robert S.; Agur, Anne M.; Loh, Eldon Y.
Abstract : Background and Objectives: Ultrasound (US)–guided diagnostic block/radiofrequency ablation (RFA) along the lateral sacral crest (LSC) has been proposed for managing sacroiliac joint (SIJ) pain. We sought to investigate (1) ease of visualization of bony landmarks using US; (2) consistency of US-guided needle placement along the LSC; and (3) percentage of the posterior sacral network (PSN) innervating the SIJ complex that would be captured if an RFA strip lesion were created between the needles. Methods: In 10 cadaveric specimens, 3 needles were placed bilaterally along the LSC from the first to third transverse sacral tubercles (TSTs) using US guidance. The PSN, SIJ, and needles were exposed, digitized, and modeled 3-dimensionally. Ease of visualization of bony landmarks, frequency of needle placement along the LSC, and percentage of the PSN that would be captured if an RFA strip lesion were created between the needles were determined. Results: The LSC, TST2, TST3, and first to third posterior sacral foramina were easily visualized using US; TST1 was somewhat obscured by the iliac crest in some specimens. Needles were placed along the LSC in 18 of 20 specimens; in the first 2 of 20 specimens, needle 1 was placed at the L5/S1 facet joint. On average, 93% (95% confidence interval, 87%–98%) of the PSN would be captured if an RFA strip lesion were created between the needles. Conclusions: The findings suggest that US-guided needle placement along the LSC is consistent and could capture most or all of the PSN. A clinical study evaluating the outcomes of this technique is in progress.